Key factors influencing the incidence of hemolysis: A critical appraisal of current evidence. (2nd January 2017) - McCaughey, Euan James; Vecellio, Elia; Lake, Rebecca; Li, Ling; Burnett, Leslie; Chesher, Douglas; Braye, Stephen; Mackay, Mark; Gay, Stephanie; Badrick, Tony; Westbrook, Johanna; Georgiou, Andrew
Abstract: Hemolysis is a leading cause of pre-analytical laboratory errors. The identification of contributing factors is an important step towards the development of effective practices to reduce and prevent hemolysis. We performed a review of PUBMED, Embase, Medline and CINAHL to identify articles published between January 2000 and August 2016 that identified factors influencing in vitro hemolysis rates. The 40 studies included in this review provide excellent evidence that hemolysis rates are higher in Emergency Departments (EDs), for non-antecubital draws, for specimens drawn using an intravenous catheter compared to venipuncture and for samples transported by pneumatic tube compared to by hand. There is also good evidence that hemolysis rates are higher when specimens are not collected by professional phlebotomists, larger volume specimen tubes are used, specimen tubes are filled less than halfway and tourniquet time is greater than one minute. The results of this review suggest that hospitals and clinical laboratories should consider deploying phlebotomists in EDs, drawing all blood through a venipuncture, using the antecubital region as the optimum blood collection site and transporting specimens by laboratory assistant/other personnel, or if this in not practical, ensuring that pneumatic transport systems are validated, maintained and monitored. Studies also recommend making hemolysis a hospital-wide issue and ensuring high-quality staff training and adherence to standard operating procedures to reduce hemolysis rates. Awareness of the factors that influence hemolysis rates, and adoption of strategies to mitigate these risk factors, is an important step towards creating quality practices to reduce hemolysis rates and improve the quality of patient care.